Maternal and Fetal Death following Group A Streptococcal Meningitis in Mid-Term Pregnancy - Sayinthen Vivekanantham; Nadeesha Mudalige; Venothan Suri; Abderahman Kamaledeen; Penelope Law (Case Reports in Obstetrics and Gynecology)
Background. Group A streptococcal (GAS) meningitis is rarely seen in the antenatal period, but it is associated with significant mortality. We present a case of a mid-trimester woman who developed fulminant meningitis following a rapid onset atypical presentation of infection with this organism. Case. A multiparous 23+5-week woman presented with a 10-day history of a non-productive cough associated with pyrexia. Within minutes of her admission she collapsed and lost consciousness; sepsis was suspected and cross-specialty care was initiated. She was managed empirically in extremis with broad-spectrum antibiotics and mannitol with 3% hypertonic saline for suspected infection and raised intracranial pressure, respectively. Despite intensivist management, a CT head revealed diffuse oedema with coning of the cerebellar tonsils. Brainstem death was certified within 19 hours of admission and fetal death ensued. Postmortem bacteriology confirmed GAS meningitis. Conclusion. Through raising awareness of this patient and her disease course, we hope that future policy decisions, primary care, and hospital level management will be informed accordingly for treatment of pregnant women with suspected GAS infection.